Effect of acute heat stress on heat shock protein 70 messenger RNA and on heat shock protein expression in the liver of broilers - Gabriel, J. E.; Ferro, J. A.; Stefani, RMP; Ferro, MIT; Gomes, S. L.; Macari, Marcos [UNESP] (Carfax Publ Co, 1996)
1. The synthesis of heat shock protein 70 (Hsp70) mRNA and the expression of Hsp70 in the liver of broiler chickens submitted to acute heat stress (35 degrees C for 5 h) was investigated.2. Hsp70 expression was detected by SDS-PAGE and Western blot analysis using a polyclonal antiserum against Hsp70 of Blastocladiella emersonii. The specific signal of Hsp70 mRNA was analysed by Northern blot using as probe a Hsp70 cDNA of B. emersonii.3. An increase in the amount of Hsp70 was detected from the first up to the fifth hour of acute heat exposure. This increase in the amount of Hsp70 was accompanied by an increase in Hsp70 mRNA which peaked at 3 h.4. This study shows that the heat induced increase in Hsp70 mRNA and protein in broiler liver, in vivo, are time dependent, similar to that in mammals.